2019
DOI: 10.1111/jora.12511
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Curiosity in the Sociopolitical Development of Black and Latinx Adolescents

Abstract: Sociopolitical development, the process of coming to understand and take action against systems of oppression, is associated with key outcomes for youth. Although rooted in Paulo Freire's work on critical consciousness, sociopolitical development models overlook a motivational attribute—curiosity—that Freire characterized as a catalyst of such development. This longitudinal study investigated the relationship between curiosity and two aspects of sociopolitical development (social analysis, societal involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…In the sample of Black adolescents, structural attributions increased from 10th to 12th grade, while individual attributions remained constant. Consistent with these findings, Clark and Seider’s (2020) longitudinal study showed that both Social Analysis and Societal Involvement generally increased over the course of high school; for Social Analysis only, the rate of change was lower for youth who started high school with higher Social Analysis scores. In addition, Social Analysis and Society Involvement were correlated at baseline and over time.…”
Section: Systematic Review Of the Critical Consciousness Literature I...supporting
confidence: 60%
See 3 more Smart Citations
“…In the sample of Black adolescents, structural attributions increased from 10th to 12th grade, while individual attributions remained constant. Consistent with these findings, Clark and Seider’s (2020) longitudinal study showed that both Social Analysis and Societal Involvement generally increased over the course of high school; for Social Analysis only, the rate of change was lower for youth who started high school with higher Social Analysis scores. In addition, Social Analysis and Society Involvement were correlated at baseline and over time.…”
Section: Systematic Review Of the Critical Consciousness Literature I...supporting
confidence: 60%
“…A longitudinal study by Clark and Seider (2020) examined the relations between curiosity and sociopolitical development in a sample of majority low-SES youth of color, who were surveyed at the beginning and end of 9th grade and the end of 10th, 11th, and 12th grades. Outcome measures included Social Analysis and Societal Involvement.…”
Section: Beliefs Knowledge and Knowledge Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, researchers have demonstrated that SPD is associated with career outcomes, such as critical consciousness, academic achievement, occupational attainment, and the pursuit of knowledge and new experiences (Clark & Seider, 2019;Dee & Penner, 2017;Diemer et al, 2009;Diemer & Li, 2011). Diemer and Blustein's (2006) study of urban poor Youth of Color found that those with higher levels of critical consciousness and SPD were more likely to view work as important in their futures and had a stronger sense of vocational identity.…”
Section: Sociopolitical Development and Social Cognitive Career Theorymentioning
confidence: 86%